The role of endobronchial ultrasound-guided transbronchial needle aspiration in the differential diagnosis of isolated mediastinal and/or hilar lymphadenopathy - Temiz, Dilek; In, Erdal; Kuluozturk, Mutlu; Kirkil, Gamze; Artas, Gokhan; Turgut, Teyfik; Deveci, Figen (Wiley, 2021)
Introduction Isolated mediastinal and/or hilar lymphadenopathy (IMHL) has become an increasingly common finding as a result of the increased use of thoracic imaging modalities. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is accepted as the first step diagnostic method in the differential diagnosis of IMHL. Objective To determine the diagnostic yield of the procedure and to analyze clinical and sonographic findings that can be used to differentiate the etiology of lymph node pathologies. Methods Patients who underwent EBUS-TBNA procedure between March 2017 and March 2020 were included in this retrospective study. Demographic data, symptoms, comorbid diseases, and EBUS findings were obtained from the records of the patients. Results EBUS-TBNA provided a diagnosis in 88 patients out of 120 patients (granulomatous diseases n = 54, malignant diseases n = 21, and anthracotic lymph nodes n = 13), and 32 patients had a negative EBUS-TBNA. 22/32 negative EBUS-TBNA samples were true negatives (reactive lymphadenopathy). The sensitivity of the procedure was 89.8% while negative predict value was 68.7%, diagnostic yield of 91.6%. Patients with reactive lymph nodes had significantly more comorbidities (77.3%-19.4%, p < .001) and a lower number of lymph node stations (1.6 +/- 0.8-2.7 +/- 0.9, p < .001). Patients with anthracotic lymph nodes were older and mostly consisted of females (11/13, p < .001). Conclusion EBUS-TBNA has high-diagnostic efficiency in the differential diagnosis of IMHL. The number and size of lymph node stations can provide useful information for differential diagnosis. Clinical follow-up can be a more beneficial approach in patients with reactive and anthracotic lymph nodes before invasive sampling.
Keywords: anthracotic lymph node; endobronchial ultrasonography; mediastinal lymphadenopathy; reactive lymph node; transbronchial needle aspiration